Planning Pharmacies: An Operational Method to Find the Best Location - Tondelli, Simona; Fatone, Stefano (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The theme of the spatial distribution of the pharmacies on the territory is closely connected to urban planning and to services supply. In Italy, the regulatory change that took place in 2012, triggered partly by the need to adhere more to a constantly changing economic system, has led to a revision of the existing situation, consisting both on the method to quantify the pharmacies distribution and on the efficiency of the service. If Law 27/2012 has effectively allowed municipalities to increase the number of pharmacies that they can settle on the municipal territory, it has also started a process of rethinking the logic of pharmacies location and of their catchment areas. In this framework, the present paper aims to discuss the merits of a regulatory evolutions that sparked the process of liberalization of locations, integrating the law guidelines and goals with an operating logic process, usable and useful to translate goals into planning actions in a continuous dialogue between law and territory, constraints and opportunities, equity and accessibility of the care services. Following this logic operations, we have investigated the urban context of Castelfranco Emilia, assuming the location of new offices on the basis of pharmaceutical analyzes.